Naše izkušnje v predoperativni zamejitvi raka požiralnika z endoskopskim ultrazvokom - Ćeranić, Davorin (Zdravniški vestnik, 2006)
Background. Patients with esophageal cancer have still poor prognosis independent of form of therapy. Endoscopic ultrasonography is an excellent diagnostic tool in staging carcinoma for selecting proper therapeutically approach. Patients and methods. From January 2002 till June 2005 in 28 patients with oesophageal cancer, endoscopic ultrasound and computed tomography of the chest was performed. The purpose of the study was to compare the assesment of esophageal cancer with surgical and histopathologic findings using TNM classification. Results. Among our patients, 12 (42.9 %) have been treated surgically and 3 (10.7 %) with radiotherapy or neoadjuvant therapy, one patient (3.6 %) refused surgical treatment. Due to advanced disease or other comorbid conditions 12 patients (42.9 %) could not be treated operatively. For 6 patients (21.5 %) surgical treatment was successful and radical, but for 6 (21.5 %) of them just palliative therapy was possible. In 4 patients (14.3 %) we underestimated T-stage. In 10 patients (35.7 %) oesophagus could not be traversed due to advanced malignant stenosis. Accuracy of endosonography and computed tomography for T-staging was 67 %, for N-staging 67 % for endoscopic ultrasound. Conclusions. Endosonography is a accurate imaging method for esophageal cancer staging. The results of our analysis have shown that the disease was confirmed in advanced stage in a significant proportion of patients and that malignant stenosis could not be traversed with the conventional endosonographic instrument.
Keywords: diagnosis; Diagnostika; endoscopy; endoskopija; Endosonografija; Endosonography; Esophageal Neoplasms; Kirurgija; mortality; Neoplasm Staging; Novotvorba, stadij; novotvorbe; požiralnik; Požiralnik, novotvorbe; rak (medicina); surgery; Tomografija, radiografska, računalniška; Tomography, X-Ray Computed; tumor; ultrazvočna diagnostika; Umrljivost